Computational Investigation of the Hemodynamic Effects of the Location of a Re-Entry Tear in Uncomplicated Type B Aortic Dissection - Eunji Kim; Sung Woon Chung; Up Huh; Seunghwan Song; Chung Won Lee; Il Jae Wang; Chanhee Song; Tae Sik Goh; Jong-Hwan Park; Dongman Ryu (Bioengineering)
This study aimed to examine the hemodynamic modifications in uncomplicated type B aortic dissection in relation to the location of re-entry tears using a computational fluid dynamics simulation. The geometry of uncomplicated type B aortic dissection was reconstructed using computed tomography images. Subsequently, 10 virtual models were artificially generated with re-entry tears at various locations. The simulation results indicated that most models with re-entry tears had lower pressure and wall shear stress than those without re-entry tears. The overall pressure distribution of the true lumen was greater than that of the models without re-entry tears when the re-entry tear was placed at the end of the false lumen. Furthermore, the recirculation phenomenon in the false lumen was reduced as the re-entry tear was relocated to the distal region of the aorta. To determine whether and how to perform fenestration surgery in patients with uncomplicated type B aortic dissection, these computational results can be used as supplemental indicators. However, further validation in a larger number of patients through additional investigation is necessary.